STRATEGI PELESTARIAN WARISAN BUDAYA LOKAL: STUDI KASUS PENETAPAN ISTANA NIAT LIMA LARAS SEBAGAI CAGAR BUDAYA KABUPATEN BATU BARA - Kumala, Shinta; Suprayitno; Suri, Nursukma (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This study aims to describe the preservation strategies and the designation process of the Niat Lima Laras Palace as a cultural heritage object at the regency level in Batu Bara Regency, North Sumatra. The palace is a historical legacy of the Kedatukan Lima Laras, built by Datuk Muhammad Yuda Sri Diraja in the early 20th century. It holds significant value as a center of Malay traditional governance and as a symbol of resistance against colonialism. This research adopts a descriptive qualitative approach using a case study method. Data collection techniques include in-depth interviews, participatory observation, documentation, and literature study, analyzed using R.M. Sedyawati’s (2007) theory of cultural preservation, which emphasizes physical, social, and functional preservation. The findings reveal that the Niat Lima Laras Palace meets three key dimensions of cultural preservation: (1) historical value, due to its connection with significant local historical events; (2) socio-cultural value, as it is still used in traditional community rituals; and (3) architectural value, as it reflects a fusion of Malay, Chinese, and European architectural styles. The designation process was carried out through the inventory of Potential Cultural Heritage Objects (ODCB), field verification by the Cultural Heritage Expert Team (TACB), and formal recognition via the Batu Bara Regent's Decree No. 406/DISPORABUDPAR/2024. This study concludes that value-based preservation strategies, community participation, and inter-institutional collaboration are key to the successful safeguarding of local cultural heritage. It recommends strengthening cultural revitalization programs, promoting local historical education, and applying adaptive preservation to ensure the sustainability of this cultural site.